Effect of long-term physical training and detraining on myocyte structure and connective tissue of Wistar rat's ventricle: preliminary experiment in rats (Medical Journal of Indonesia, 2011)
Background: This study was aimed to evaluate the structural changes of the ventricular myocardium in a physiological hypertrophic heart model due to long term aerobic and anaerobic physical training and detraining. Methods: In-vivo experimental study on Wistar rats (8 weeks old), weighing 150-250 grams who were divided into 3 large groups: control group, aerobic exercise group and anaerobic exercise group. Aerobic and anaerobic training were conducted for 4 and 12 weeks. At the end of 4 and 12 weeks of exercising, half of each exercising group was sacrificed to study the morphological and histopathological changes in myocardial structure. The remaining of the groups were given a period of 4 weeks of detraining and sacrificed at the end of the 8th and 16th week. Results: Significant differences in heart weight and left ventricular wall thickness was found in the 4 weeks of aerobic and anaerobic group compared to the control group (751.0 ± 36.5 gr and 791.1 ± 15.8 gr vs 588 ± 19.4 gr ), (3.34 ± 0.12 mm and 3.19 ± 0.1 mm vs 2.80 ± 0.07 mm). An increase in heart mass weight was observed in both 12 weeks aerobic and anaerobic training group compared to the control group (1030.8 ± 82.4 gr and 1140.4 + 0.24 gr vs 871.6 ± 62.0 gr). Heart volume of the 12 weeks aerobic-anaerobic groups showed a significant increase (3.58 ± 0.31 mm and 4.04 ± 0.30 mm) compared to the control group (2.82 ± 0.14 mm). The length of cardiomyocyte was in log 10 to normalize the data. There was a significant increase in the length of the cardiac muscle cells of the 4 weeks aerobic and anaerobic group (1.09± 0.08 µm and 1.00± 0.12 µm) compared with the control group (0.73± 0.1 µm). Width of heart muscle cells in the 4 weeks aerobic-anaerobic group showed a significant increase when compared to the control group (5.38± 1.3 µm and 5.5± 2.11 µm) vs (2.74± 0.53 µm). Significant reduction in the length of cardiac muscle cells in the detrained 4 weeks aerobic group (0.94± 0.08 µm) was found when compared to the treatment group (1.09± 0.08 µm). Significant differences were found between the length of cardiac muscle cells in the 12 weeks aerobic-anaerobic groups (1.3± 0.04 µm and 1.2± 0.07 µm) compared to the control group (0.95± 0.69 µm). Significant width increments of heart muscle cells was found in the 12 weeks aerobic-anaerobic groups (7.3± 1.01 µm and 6.44± 0.08 µm) compared to the control group (4.52 ± 0.91 µm). Conclusion: Long term aerobic and anaerobic training causes an increase in both wall thickness and diameter of the leftÂ ventricular cavity, as well as slight fibrosis. The increase in wall thickness, diameter, and fibrosis diminish during detraining period. (Med J Indones 2011; 20:271-7)